SURFACE DISCHARGE CHARACTERISTICS ON THE ACRYLIC SURFACE AROUND THE EDGE OF CIRCULAR PLANE-PLANE ELECTRODES WITH AIR AND OIL INSULATION - Nurdiansyah, Rian
The quality of a power system is influenced by the resilience of the power system from disruptions that occur. One of the most influential is the issue of isolation which is very vital to the resilience of the power system. One sign of damage to an isolation is the occurrence of partial discharge (PD) which is an early warning of damage to the insulation so that preventive measures can be taken so that the damage does not get worse and spread to other electrical components. PD detection can be done by detecting radiation produced by PD, including detection of Transient Earth Voltage (TEV), or the more conventional detection of electromagnetic, acoustic and mechanical waves. PD can occur in solid, liquid and gas insulation materials. In this study measurement experiments were carried out on one type of PD namely surface discharge that occurs at the border between two insulation with different dielectric capabilities. Measurements were made using the IEC 60270 standard by detecting electrically using a HFCT (high frequency current transformer) sensor and RC detector sensor for non-electric detection using a Loop Antenna sensor. Measurements were also made on two types of insulation namely gas (air) and liquid (oil) insulation using circular plane-plane electrodes as a homogeneous and symmetrical electric field generator. The results of this study get the characteristics of surface discharge that occurs on acrylic surfaces with a homogeneous field that occurs in air isolation and oil isolators using mineral oil in the form of PDIV (partial discharge inception voltage), PD waveforms (waveform) and PD phase patterns (PD phase pattern). Based on the characteristics obtained, it can be analyzed how the mechanism of surface discharge on the acrylic surface and its reaction with the surrounding isolator.